Fungal signature differentiates alcohol-associated liver disease from nonalcoholic fatty liver disease - Greta Viebahn; Phillipp Hartmann; Sonja Lang; Münevver Demir; Xinlian Zhang; Derrick E. Fouts; Peter Stärkel; Bernd Schnabl (Gut Microbes, 2024)
ABSTRACTThe fungal microbiota plays an important role in the pathogenesis of alcohol-associated liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD). In this study, we aimed to compare changes of the fecal fungal microbiota between patients with ALD and NAFLD and to elucidate patterns in different disease stages between the two conditions. We analyzed fungal internal transcribed spacer 2 (ITS2) sequencing using fecal samples from a cohort of 48 patients with ALD, 78 patients with NAFLD, and 34 controls. The fungal microbiota differed significantly between ALD and NAFLD. The genera Saccharomyces, Kluyveromyces, Scopulariopsis, and the species Candida albicans (C. albicans), Malassezia restricta (M. restricta), Scopulariopsis cordiae (S. cordiae) were significantly increased in patients with ALD, whereas the genera Kazachstania and Mucor were significantly increased in the NAFLD cohort. We identified the fungal signature consisting of Scopulariopsis, Kluyveromyces, M. restricta, and Mucor to have the highest discriminative ability to detect ALD vs NAFLD with an area under the curve (AUC) of 0.93. When stratifying the ALD and NAFLD cohorts by fibrosis severity, the fungal signature with the highest AUC of 0.92 to distinguish ALD F0-F1 vs NAFLD F0-F1 comprised Scopulariopsis, Kluyveromyces, Mucor, M. restricta, and Kazachstania. For more advanced fibrosis stages (F2-F4), the fungal signature composed of Scopulariopsis, Kluyveromyces, Mucor, and M. restricta achieved the highest AUC of 0.99 to differentiate ALD from NAFLD. This is the first study to identify a fungal signature to differentiate two metabolic fatty liver diseases from each other, specifically ALD from NAFLD. This might have clinical utility in unclear cases and might hence help shape treatment approaches. However, larger studies are required to validate this fungal signature in other populations of ALD and NAFLD.